Poesie scelte Introduzione e traduzione con testo a fronte - Geiger, Benno (Biblioteca di Studi di Filologia Moderna, 2021)
The volume presents a selection of poems originally composed in German by Austrian-Italian author Benno Geiger and translated into Italian for the first time. This publication aims to make Geiger's poetical work available to a broader audience and place it aside his better known writing on Art History. Geiger's specific role as a mediator and bridge between two cultures makes his poetical work extremely significant, as well as considering his prolific activity as a literary translator to which he devoted himself throughout his life. The current edition provides bilingual parallel text, preceded by an introductory essay and a biographical profile of the author. The critical apparatus highlights both the intertextual references and the writer's complex links with the Italian and German poetical traditions.